Pemberian minuman formula kacang merah, kacang tanah, dan kacang kedelai terhadap status gizi ibu hamil kurang energi kronis (KEK) - Nendhi Wahyunia Utami; Tita Husnitawati Majid; Dewi Marhaeni Diah Herawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: The prevalence of malnutrition in pregnant women DIY reached 22.69%, while at Sleman amounted to 11.72%. The study has been developed drinks formula derived from beans that contain the nutrient according to the needs of pregnant women.Objective: This study aimed to analyze the influence of red beans, peanuts and soybeans drink formula against the nutritional status of pregnant women.Method: The study design is randomized controlled trial (RCT). The inclusion criteria are pregnant women with chronic energy deficiency and gestational age between 14-28 weeks. The research locations in 8 health centers in Sleman with total sample of 84 people. Data obtained by measuring LILA and pregnant women weight before and after being given a drink formula. Data analysis using Chi-Square, paired t-test and Wilcoxon.Results: There was differences between the increase of weight and LILA pregnant women in the treatment group was higher than controls (p<0.005). Increase of BB and LILA on the three groups there is a difference (p<0.001). Based on measurements of nutritional status of pregnant women showed that significant effect giving peanuts formula compared to red beans and soy bean formula that does not significantly (p<0.001). Groups of pregnant women who get peanuts formula showed increased protein intake above the standard of 67 g and a total energy of 2260 calorie.Conclusion: Nutritional status of pregnant women who get the peanut formula higher than by red beans, soy beans, and formula for pregnant women. Pregnant women who received peanuts formula have higher energy and protein intake than the other formulas.